2016
DOI: 10.18632/oncotarget.13304
|View full text |Cite
|
Sign up to set email alerts
|

Cold atmospheric plasma, a novel promising anti-cancer treatment modality

Abstract: Over the past decade, cold atmospheric plasma (CAP), a near room temperature ionized gas has shown its promising application in cancer therapy. Two CAP devices, namely dielectric barrier discharge and plasma jet, show significantly anti-cancer capacity over dozens of cancer cell lines in vitro and several subcutaneous xenograft tumors in vivo. In contrast to conventional anti-cancer approaches and drugs, CAP is a selective anti-cancer treatment modality. Thus far establishing the chemical and molecular mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
407
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 443 publications
(427 citation statements)
references
References 162 publications
(349 reference statements)
12
407
0
8
Order By: Relevance
“…As previously mentioned, CAP is also used for anticancer therapy [20][21][22][23]. Vitamin C has also been suggested to have adverse effects on cancer cells [28].…”
Section: Combining Vitamin C With Cold Atmospheric Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned, CAP is also used for anticancer therapy [20][21][22][23]. Vitamin C has also been suggested to have adverse effects on cancer cells [28].…”
Section: Combining Vitamin C With Cold Atmospheric Plasmamentioning
confidence: 99%
“…It has been demonstrated that cold plasma can induce necrosis, apoptosis and cell detachment by disrupting certain phases of tumor cell replication [20]. CAP effectiveness has been demonstrated against dozens of tumor cell lines and tumor types in vitro and in vivo, respectively [21]. The unfortunate limitation in the use of CAP against tumors is that a high dose CAP exposure can also harm healthy mammalian cells [20], hence the need for precise micro devices.…”
mentioning
confidence: 99%
“…Cold atmospheric plasma (CAP) has been extensively studied for its biomedical use in various fields such as surface decontamination [5], wound healing [6,7], dental treatment [8], allergen destruction [9], HIV virus treatment [10] and among others [11]. In particular, the research of CAP as a potential oncotherapeutic approach has thrived over the past decade and the mechanism is been increasingly understood [12][13][14][15][16]. It is widely reported that CAP deactivated more than 20 types of cancer in vitro by inducing apoptosis [17][18][19], cell cycle arrest [20][21][22], endoplasmic reticulum stress [23,24] and DNA damage [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The observed beneficial effects in wound healing [4][5][6] and cancer [7][8][9] have significantly spurred research efforts and novel findings in recent years. Promising in vitro research investigations are an ethical and scientific necessity for translation of plasma applications to in vivo models and eventually to humans.…”
Section: Introductionmentioning
confidence: 99%